An Analysis of the Process of Nurse Practitioners Moving to Full Practice Authority and Developmental Summary of Practice Implications to Assist Others in the Future - Woodley, Lisa (My University, 2017)
Abstract Nurse Practitioners (NPs) have assumed a progressively important role as primary care providers for millions of Americans. Full practice authority (FPA) is the collection of state practice and licensure laws that allow NPs to use their training to the fullest extent. The purpose of this scholarly project is to explore the positives, barriers, or issues the preceding states and Washington District of Columbia (DC) faced transitioning from restrictive or reduced practice to FPA. An analysis, including key findings to assist with future transitioning will be provided. An extensive search of white papers, reports, newspapers, blogs, and websites to gain information for this subject was conducted. Personal interviews and communications with each of the FPA states was sought through their advanced nurse practitioner association or their advanced practice nursing council for more descriptive insight to each states experience. The results of this project provide an effective model for transition for the remaining states without FPA. Keywords: full practice authority, restrictive or reduced practice, transitioning
Keywords: full practice authority, restrictive or reduced practice, transitioning